2022
DOI: 10.1155/2022/8118408
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effectiveness and Safety of Chinese Herbal Medicine Compound Kushen Injection as an Add-On Treatment for Breast Cancer: A Systematic Review and Meta-Analysis

Abstract: Objective. To systematically evaluate the effect and safety of compound Kushen injection (CKI) as an add-on treatment on the treatment for breast cancer. Methods. We searched eight major electronic databases from their inception to November 1, 2021, for randomized clinical trials (RCTs) comparing CKI plus chemotherapy with chemotherapy alone. Primary outcomes included objective response rate (ORR) and disease control rate (DCR), health-related quality of life (HRQoL), progression-free survival (PFS), and overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…However, recent evidence proposes that TEAM used in different stages of cancer lesions might be beneficial to the entire course of cancer prevention and treatment, including recovery from post-operation, and when undergoing radiotherapy or chemotherapy ( Qi et al, 2015 ). Previous studies on the effect of TEAM combined with conventional cancer treatment on postoperative recurrence and survival have been reported in non-small cell lung cancer ( Kawai and Saito, 2020 ), hepatocellular carcinoma ( Zhao et al, 2020 ), bladder cancer ( Chen et al, 2014 ), and breast cancer ( Wang et al, 2015 ; Zhu et al, 2016 ; Ho et al, 2021 ; Lai et al, 2022 ). A phase IB trial conducted in the United States reported that an aqueous extract of S. barbata was well tolerated and showed promising clinical evidence of anticancer activity in patients with metastatic breast cancer ( Perez et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent evidence proposes that TEAM used in different stages of cancer lesions might be beneficial to the entire course of cancer prevention and treatment, including recovery from post-operation, and when undergoing radiotherapy or chemotherapy ( Qi et al, 2015 ). Previous studies on the effect of TEAM combined with conventional cancer treatment on postoperative recurrence and survival have been reported in non-small cell lung cancer ( Kawai and Saito, 2020 ), hepatocellular carcinoma ( Zhao et al, 2020 ), bladder cancer ( Chen et al, 2014 ), and breast cancer ( Wang et al, 2015 ; Zhu et al, 2016 ; Ho et al, 2021 ; Lai et al, 2022 ). A phase IB trial conducted in the United States reported that an aqueous extract of S. barbata was well tolerated and showed promising clinical evidence of anticancer activity in patients with metastatic breast cancer ( Perez et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported enhanced tumor response, improved quality of life, and reduced risk of adverse events in patients with breast cancer, on evaluating the effects of TEAM combined with chemotherapy compared with chemotherapy alone. However, long-term survival data were unavailable ( Zhu et al, 2016 ; Lai et al, 2022 ). Moreover, most reviews did not separately quantify the clinical benefits of TEAM according to the stage or subtype of breast cancer ( Wang et al, 2015 ; Zhu et al, 2016 ; Ho et al, 2021 ; Lai et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of a previous study demonstrated numerous pharmacological properties of CKI, including antitumor, analgesic, immunity-enhancing and anti-inflammatory activities ( 14 ). CKI is extensively used in the treatment of numerous malignancies, including breast, lung and liver cancer ( 15 ). CKI is often used alone, or in combination with chemotherapy or radiotherapy ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although effective, medications are also associated with adverse effects and cost, as well as challenges with patient compliance [ 7 ]. On the other hand, herbal medicine with adequate clinical effectiveness and low toxicity has been used as an alternative to treat diseases [ 8 , 9 ]. Natural compounds such as flavonoids are becoming increasingly popular.…”
Section: Introductionmentioning
confidence: 99%